Conversational Shadows: Describing Live Media Events Using Short Messages - Shamma, David; Kennedy, Lyndon; Churchill, Elizabeth (Proceedings of the International AAAI Conference on Web and Social Media, 2010)
Microblogging concurrently with live media events is becoming commonplace. The resulting comment stream represents a parallel, social conversational reflection on the event. Although not formally `attached’ to the actual event stream itself, we demonstrate it is possible to establish a relationship between the two streams by mapping their structural properties. In this article, we examine: How do people produce and consume real-time commentary? And how does the structure of commentary and conversation change in response to moments of interest? Using a dataset of 53,712 Twitter posts, or tweets, sampled during the inauguration of Barack Obama in January 2009, we develop methods for exploring these questions. We find that short message activity reflects the structure and content of this media event. Specifically, messages directed at large audiences can serve as broadcast announcements, while variations in the level of conversation can reflect levels of interest in the media event itself. Finally, we present some implications for the design of future tools for a variety of users ranging from consumers to journalists.